GPS-based incident detection algorithm for two-lane bus rapid transit systems: case study of Istanbul Metrobus - Goncu, Sadullah; Sahin, Ismail (SPRINGER HEIDELBERG, 2024)
Bus rapid transit (BRT) systems have been gaining popularity in both developed and developing countries, having system deployments on varying scales. Especially in developing economies, BRT systems provide an easy solution to mobility needs. However, depending on their geometric design and operational characteristics, BRT systems may be vulnerable to incidents within their right-of-way. Even combined with excessive demand and exclusive corridor design, an incident inside the BRT corridor can cause significant delays to the commuters. Through this paper, we aim to propose a GPS-based incident detection algorithm for BRT systems. The proposed detection scheme is tested through a real-world case study conducted on the Istanbul Metrobus system through 19 real-world incident records. The results for the proposed algorithm are comparatively evaluated with another GPS-based incident detection scheme from the literature. The resulting performance measures of the proposed algorithm obtained as 100% detection rate, 0.74% false alarm rate, and 2.9-min mean time to detection.
Keywords: Public transport; Bus rapid transit; Incident detection; GPS; BRT; Transportation